Penerapan Media Chromebook Berbasis Quizizz Untuk Meningkatkan Minat Belajar Materi Fiqih Madrasah Aliyah - Salsabila, Ailsa Hayati Marsa; Syarif, Zainuddin (Journal of Instructional and Development Researches, 2025)
This study aims to describe the implementation of Quizizz-based Chromebooks in Fiqh learning in class X of Madrasah Aliyah as a strategy to increase student interest and engagement. The problem of low learning enthusiasm arising from the dominance of the lecture method is the basis for conducting this study. The method used is qualitative with a descriptive approach, involving Fiqh teachers and students as data sources through observation, semi-structured interviews, and documentation. The results of the study indicate that the use of Chromebooks supported by the Quizziz application can create a more interactive learning atmosphere, foster motivation, and help students understand the material through direct feedback. Teachers benefit from the reporting feature that facilitates the process of evaluating learning outcomes in a more targeted manner. Overall, this integration of digital technology shifts Fiqh learning from traditional patterns to a more varied, active approach that suits the character of the current generation.